Assessment of Pitman Model Capabilities in Modelling Surface Water-Groundwater Interactions in the Lake Sibaya Catchment, South Africa - Ramatsabana, Phatsimo Pearl (Rhodes University, Faculty of Science, Institute for Water Research)
Difficulties arising from data scarcity, input data error or uncertainty, heterogeneous environments, lack of process understanding, and model structural uncertainty frequently constrain hydrological assessments of South African catchments. This research aimed to assess the usefulness of a "simpler" conceptual model for the conjunctive management of surface water and groundwater. The idea is that, to leverage the limited available data and information, a compromise between model complexity and data availability is required, which improves the use of models to produce reliable hydrological systems assessments. The research methodology focused on catchment-scale lake-groundwater dynamics to explore the limits of the groundwater components of the modified Pitman model (Hughes, 2004) in this type of environment, thus, determining the potential for using this model for integrated water assessments in South Africa. The Pitman model (Pitman, 1973; Hughes, 2013) is one of the most widely accepted models regarding surface water hydrology in South Africa; however, the newly incorporated groundwater components (Hughes, 2004) have not been applied as extensively as the surface water components. There remains uncertainty regarding their capability to adequately simulate groundwater processes and accurately represent surface and groundwater interactions in some environments. The model was assessed based on how well simulated water balance variables accurately reflected available evidence and expected catchment response (objective 1). Secondly, the research identified and addressed uncertainties as regards the structure and application of the model's groundwater interaction components (objective 2). The model was set up for the Lake Sibaya catchment, which is a predominantly groundwater-driven system and, thus, provides an important opportunity to interrogate different aspects of uncertainty in both the conceptualizing and quantifying interaction processes. The study's overall conclusion is that the model performed satisfactorily as it was able to simulate the lake's water balance correctly enough such that the influences of dominating components were sensibly reflected in variations in streamflow and lake volumes. The following key findings were noted; (i) the lake volume shows a continuous decline, (ii) the lake volume decreased with increasing development (forestry and abstractions) in the lake catchment, (iii) there is significant rainfall uncertainty in the study area and the model showed high sensitivity to rainfall differences, (iv) robust conceptual knowledge of local catchment conditions was valuable for reducing some of the data related uncertainty in the study area and for producing realistic model simulations, (v) the Pitman model (Hughes, 2013) updated GW components can provide a valuable tool for modelling integrated hydrological processes; nevertheless, when applying the model to specific environments, implicit approaches may be necessary to account for processes that are not fully represented in the model.
Keywords: Hydrologic models -- South Africa Sibayi, Lake; Groundwater Management; Surface water management; Groundwater flow; Watershed management -- South Africa